Situation Analysis of Midea Company - Yuhang Shen (Journal of World Economy, 2024)
Midea Group, one of the famous companies in China, is known for its outstanding achievements in the field of household appliance. Under the guidance of diversification strategy, it has successfully occupied a broad market share and shown remarkable growth potential. Looking into the future, with the in-depth development of global economic integration and the continuous progress of science and technology, Midea will continue to adhere to the innovation-led development, constantly promote the upgrading of products and services, and is committed to building the world’s leading provider of household appliances and intelligent solutions. This article is aimed to conduct a comprehensive situation analysis of Midea. In this article, the overall information of Midea will be displayed, including its ownership structure, vision, mission, and core values, etc., so that readers can have a detailed understanding of the company. In addition, Midea’s product analysis, industry and market analysis will be performed, so that its marketing situation and competitive advantages can be further analyzed. Finally, two critical success factors of Midea will be listed to identify the reasons for its current success and strong market share. Also, in order to ensure its future performance growth, industry-related concerns and market-related concerns will also be discussed to analyze some potential risks and strong competitors.